Morphometric study of suprascapular notch - R Vandana; Sudha Patil (Wolters Kluwer Medknow Publications, 2013)
Background and aims: Suprascapular nerve may be compressed anywhere along its course but most commonly at the level of SSN (suprascapular notch) and spinoglenoid notch. The variation in the morphological and morphometric features of SSN, spinoglenoid notch, therefore plays a crucial role in the suprascapular nerve entrapment syndrome.The purpose of present study was to determine the variation in morphology and dimensions of SSN and to determine posterosuperior and posterior limits of safe zone for shoulder joint procedures from posterior approach. Material & methods: We conducted study on 134 dry scapulae of north Karnataka region and classified the SSN into various shapes according to Iqbal et al and I-VI types based on description by Natsis et al, along with this, the mean distance from the SSN to supraglenoid tubercle and the mean distance between posterior rim of glenoid cavity and medial wall of spinoglenoid notch at the base of scapular spine were also measured. Results: Based on Iqbal et al classification, 'U' shaped notch found to be most common (35%) whereas least common was W shaped (0.7%).The incidence of complete ossification of STSL was 12.6%. Based on Natsis classification most common was type II (TD>VL) seen in69% and least common was type VI (notch & foramen) 0% .The mean distance from SSN to supraglenoid tubercle was 27.3 mms ±1.7 and mean distance between posterior rim of glenoid cavity and medial wall of spinoglenoid notch at the base of scapular spine was 13mms ± 0.2 which are comparatively less than the other population studies which are mentioned in the article. Conclusions: There are variations in the shape and size of SSN and safe zone critical distance in different populations so it requires still more population specific studies on suprascapular notch.